First Record of Parambassis lala (Hamilton, 1822) from the Upper Krishna River Basin, Maharashtra, India - Shelake, Sachin; Deshpande, Vishwas (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2025)
The present study documents the first occurrence of the high-fin glassy perchlet, Parambassis lala (Hamilton, 1822), in the Upper Krishna River Basin, located in Maharashtra, India. This species is a small, translucent freshwater fish belonging to the family Ambassidae, previously known from the Gangetic plains, Brahmaputra drainage, and other eastern regions of the Indian subcontinent. Its occurrence in the northern Western Ghats represents a considerable westward extension of its known geoical distribution and suggests a potential shift in the ecological boundaries of the species. Field surveys conducted between 2022 and 2024 at multiple sites along the Krishna River and its tributaries led to the collection of specimens from slow-flowing, well-vegetated sections of the river. The collected individuals were morphologically identified based on diagnostic characters such as a prominently elevated dorsal fin, deeply compressed translucent body, and standard meristic features, and were further verified using regional taxonomic keys. The detection of P. lala in the Upper Krishna Basin may point to one of two possibilities: an anthropogenic introduction, potentially through the ornamental fish trade or inadvertent release via aquaculture systems, or a previously undocumented natural dispersal, indicating a broader ecological tolerance and adaptability than previously recognized. This study not only contributes to the ichthyofaunal inventory of the Krishna River Basin but also underscores the importance of regular biodiversity surveys in detecting biogeoic anomalies and informing conservation efforts. Continued research is essential to understand the population dynamics, reproductive ecology, and potential ecological impacts of P. lala in this newly colonized habitat.